The Debt Repayment on a Murabaha Financing Debt before Maturity Date: A Regulatory Approach and Its Compliance - Alfi Husni; Khairiyah, Septa Hanum; Azzam Fawwaz (IJISH (International Journal of Islamic Studies and Humanities), 2025)
This study explores how murabaha financing is applied in Islamic financial institutions after the release of DSN-MUI Fatwa No. 153/2022 and the 2023 OJK Murabaha Financing Guidelines. These new rules aim to ensure stronger Sharia compliance by providing clear procedures for early debt settlement, margin discounts, and repayment arrangements. With a more transparent and standardized framework, the regulations are expected to reduce disputes, improve efficiency, and bring greater consistency across institutions. Using a qualitative approach, this research reviews regulatory documents, institutional Standard Operating Procedures (SOPs), and actual practices in selected Islamic banks and financing companies. The findings show that the updated guidelines encourage institutions to adjust their SOPs to align with both Sharia principles and operational best practices. Standardizing settlement and discount methods improves transparency, removes uncertainties, and builds customer trust. The results also highlight how clear regulations can support financial stability in the Islamic banking sector by ensuring murabaha transactions are fair, predictable, and fully compliant with Sharia. Overall, this study offers practical insights for policymakers, Sharia boards, and practitioners on how regulatory clarity can strengthen both operational performance and religious adherence in Islamic finance.